Luther on vocation, by Gustaf Wingren: A twenty‐first‐century theological‐literary reading. Issue 2 (19th June 2018) - Persaud, Winston D.
Abstract: In this article, the author offers a critical, appreciative appraisal of The One Mediator, Luther on Vocation, by Gustaf Wingren (English translation, 1957), which continues to be a seminal text for understanding Luther's teaching on the theme of vocation. The author points out that the reader needs to keep in mind both the difference between Luther's world of the sixteenth century and the world of the early twenty‐first century, and the sobering reality that pursuing the neighbor's good continues to be an essential, definitive calling that every Christian has. Further, the author calls attention to Wingren's indisputable reminder that, for Luther, vocation is about the way of the Christian in human society. That way of being in pursuit of the neighbor's good is consequent upon the forgiveness of sins, which God bestows on the sinner who receives it through faith in Jesus Christ. It is God alone who is the decisive actor, even though in the former—seeking the neighbor's good—God's work is hidden; that is, the human actor is a "mask of God."